Thank you for the opportunity to help you with your question!
In order to prove that f(x) is inverse of g(x), we have to show f(g(x)) = g(f(x))
f(x) = -x/4 and g(x) = -4x
f(g(x)) = f(-4x) = -(-4x)/4 = x
g(f(x)) = g(-x/4) = -4*(-x/4) = x
As f(g(x)) = g(f(x))
Hence f and g are inverses of each other.
f(x) = (x+3)/2 and g(x) = 2x+3
f(g(x)) = f(2x+3) = (2x+3+3)/2 = x+3
g(f(x)) = g((x+3)/2) = 2*(x+3)/2 +3 = x+6
As f(g(x)) is not equal to g(f(x))
Hence f and g are not inverses of each other.
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?